Efeito do condicionamento com diferentes concentrações de ácido fluorídrico na adesão e na resistência à flexão de uma cerâmica feldspática - Venturini, Andressa Borin (2014)
Purpose: To evaluate the effect of different hydrofluoric (HF) acid concentrations in the contact angle and in the durability of bond strength between feldspathic ceramic and resin cement, as well as the impact on the roughness and flexural strength of this ceramic. Materials and Methods: Twenty-five ceramic blocks (VitaBlocks Mark II) (12 x 10 x 2.4 mm) were produced for contact angle analysis, 40 ceramic blocks (12 x 10 x 4 mm) for microtensile bond strength (MTBS), and 150 ceramic barshaped specimens (14 x 4 x 1.2 mm) to evaluate the roughness and flexural strength. Specimens were randomly divided into 5 groups, excluding the control group for MTBS: SC (control) - no ceramic surface treatment; etching with HF acid 1% (HF1), 3% (HF3), 5% (HF5) and 10% (HF10) for 60. The contact angle measurements were performed on a Goniometer and the MTBS test in a universal testing machine. All bar-shaped specimens were analyzed in a profilometry and loaded to failure using a 3-point bending test. Data were submitted to statistical analysis. Results: SC had the highest contact angle (61.4°± 5°), whereas HF10 showed the lowest value (17.5° ± 4°). In dry conditions, different HF acid concentrations promoted similar bond strength statistically (14.2 to 15.7 MPa) (p<0.05), but when the specimens were aged, only the bond from the HF1 group decreased statistically (14.5 to 10.2 MPa). All groups produced significantly rougher surfaces than the control group (SC) (p<0.05). However, the mean flexural strength values were not statistically different among the etched groups (106.47 to 102.02 MPa). Conclusion: In terms of adhesion, the tested ceramic can be etched with HF acid in concentrations of 3%, 5% and 10%. Different acid concentrations did not affect the flexural strength of the tested ceramic. Acid etching appear to have a weakening effect on the ceramic surface, if compared to the untreated group.